ASSESSING ALUMNI’S SATISFACTION ON TRAINING ACTIVITIES AT HAI DUONG CENTRAL COLLEGE OF PHARMACY (Vietnam Journal of Community Medicine, 2022)
Objective: Determining the factors affecting the satisfaction and analyzing Alumni’s satisfaction ontraining activities at Hai Duong Cental Collegge of Pharmacy.Methods: A cross-sectional study was conducted on 282 regular college students of Course 10, HaiDuong Central College of Pharmacy who graduated in September 2020 (Alumni).Results: There are 4 factors affecting Alumni’s satisfaction with training activities at Hai DuongCentral College of Pharmacy with statistical significance in order of influence: (1) Teaching staff,(2) Training program, (3) Facilities & career guidance activities and (4) Support process andactivities. These 4 factors explain 68,5% of the variation Alumni’s satisfaction. In addition, thestudy also shows that the employment status is a factor that effects the Alumni’s satisfaction, thealumni group with a job that is suitable for the training major feels more satisfied than the alumnigroup without a job.
Keywords: Alumni, satisfaction, training activities.